HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN AKIBAT HOSPITALISASI PADA ANAK DI USIA PRA SEKOLAH Di IRINA E BLU RSUP Prof Dr.R.D KANDOU MANADO - Lumiu, Stella E.; Tuda, Josef; Ponidjan, Tati (Universitas Sam Ratulangi)
Abstract: Family is a collection of two or more people, who each other are emotionally attached to eachother, as well as the same residence in an adjacent area. Family support is an attitude, actionand acceptance of the family members. Anxiety is an individual response to a state that is notpleasant and experienced by all living things in everyday life. The purpose of this study to determine the relationship of family support with levels of anxiety due to hospitalization at preschool age children in Irina E Blu Hospital Prof. Dr. RD Kandou Manado. Methods This study is a descriptive analytic cross sectional study. Accidental sampling technique that sampling with a sample of 30 respondents.Results: The statistical test used in this study is the result of Chi Square (X2) is 4,455 with a significant level of p = 0, 035 because of p <0.05 which means that there is a relationship between the level of family support with anxiety due to hospitalization in children aged pre-school BLU Prof Dr Dr.RD Kandou Manado. Conclusion the better support provided by the family can reduce the level of anxiety in children who experienced hospitalization. Keywords: Family Support, Performance Anxiety, Children in pre-school age are experiencing hospitalization. Â Abstrak: Keluarga adalah kumpulan dua orang manusia atau lebih, yang satu sama yang lain saling terikat seacara emosional, serta bertempat tinggal yang sama dalam suatu daerah yang berdekatan. Dukungan keluarga adalah sikap, tindakan dan penerimaan keluarga terhadap anggotanya.Kecemasan merupakan respon individu terhadap suatu keadaan yang tidak menyenangkan dan dialami oleh semua makhluk hidup dalam kehidupan sehari-hari. Tujuan penelitian ini untuk mengetahui hubungan dukungan keluarga dengan tingkat kecemasan akibat hospitalisasi pada anak usia pra sekolah di Irina E Blu Rsup Prof Dr R.D Kandou Manado. MetodePenelitian ini bersifat deskriptif analitik dengan rancangan cross sectional study.Teknik pengambilansampel yaitu aksidental sampling dengan sampel sebanyak 30 responden. Hasil: Uji statistik yang digunakan dalam penelitian ini adalah Chi Square dengan hasilÂ (X2) adalah 4.455 dengan tingkat signifikansi p=0, 035 oleh karena p< 0,05 yang berarti bahwa ada hubungan antara dukungan keluarga dengan tingkat kecemasan akibat hospitalisasi pada anak usia pra-sekolah BLU RSUP Prof Dr.R.D Kandou Manado.Kesimpulan semakin baik dukungan yang diberikan oleh keluarga dapat mengurangi tingkat kecemasan pada anak. Kata Kunci: Dukungan Keluarga, Tingkat Kecemasan ,Anak diusia pra-sekolah yang mengalami hospitalisasi.